Extent and pattern of burden of care and its associated factors among Eritrean families of persons living with schizophrenia: a cross-sectional study - Xiaofeng Li; Tesfaldet Habtemariam Hidru; Mohammed Hamid Osman; Sainyugu Lolokote (BMJ Open)
Purpose To assess the caregiving burden and its associated factors among Eritrean families of persons living with schizophrenia.Methods A cross-sectional study was conducted for 146 caregivers with their respective known patients with schizophrenia of Saint Mary's Neuropsychiatric National Referral Hospital (SMNNRH). Data were collected using Pai and Kapur's Family Burden Interview Schedule (FBIS), the Positive and Negative Syndrome Scale (PANSS) and self-prepared sociodemographic sheet. Data were analysed using SPSS V.21. Descriptive statistics, independent t-tests, one-way analysis of variance (ANOVA) and multiple regression analysis was employed to analyse the data.Results In this study, 84 (57.5%) were males and 62 (42.5%) were females. The mean age was 33.96+10.37 (median=31) for the patients and 46.76+13.96 (median=48) for the caregivers. Total mean objective score was 29.47+6.67. Family caregivers who were single (F=3.224, p<0.005, effect size (ES)=0.064), had educational level at elementary (F=5.647 p=0.001, ES=0.11), had low monthly income (t=7.727, p<0.001, ES=0.01) and were dissatisfied with family support (t=2.889, p<0.01, ES=0.01) experienced greater burden relative to the counterparts. Caregiver's age (β=0.156; p<0.05), duration of caregiving (β=0.131; p<0.05), monthly household family income (β=−0.298; p<0.001), history of self-injury (β=0.151; p=0.05), positive scale (β=0.344; p<0.001), negative scale (β=0.278; p<0.001) and general psychopathological scale (β=0.146; p<0.01) emerged as significant predictors of objective burden.Conclusions Family caregivers of a person living with schizophrenia experience a significant burden of care. Our findings highlight that there is a need of strengthening social and psychological support to reduce the caregiving burden.